Penyuluhan Penerapan Undang Undang No.19 Tahun 2016 Pada Media Sosial di SMP Swasta Nasrani 1 Medan - Sumiaty Hutabarat; Anda Yanni (JPM: Jurnal Pengabdian Masyarakat, 2023)
The use of the Internet is not a new thing for today's young generation. Social media is scrambling to attract consumers' interest, starting from attractive features, as a media for promotion, as a forum for communication gatherings within groups, to providing useful information in the form of photos, writings and videos. The use of the internet has become a basic need for students so that more internet users come from among students. But unfortunately the younger generation has not been able to use the internet wisely, so we can see various cases that have befallen students regarding the use of social media to drag them into the realm of law. Social media, which initially had the benefit of imparting knowledge, has become an arena for showing off and a venue for spilling inappropriate sentences and words to each other. The increasing prevalence of violations committed by students has prompted the government to issue the ITE (Information and Electronic Transactions) Law. Today's students do not fully understand these laws, so we, from the STMIK Budi Darma Community service team, provide counseling on the Implementation of Law no 19 of 2016 at Christian 1 Medan Private Middle School which aims to make students understand these laws and be wiser in using the internet.